Routine Laboratory Testing Role For Covid-19 Identification: A Systematic Review - Pratama Umar, Tungki; Siburian, Reynold (Medical Science Journal for Advance Research, 2022)
Introduction: Coronavirus disease 2019 (COVID-19) is the cause of undergoing pandemic. Molecular testing in the form of reverse transcription-polymerase chain reaction (RT-PCR) is considered as the diagnostic standard for detecting COVID-19. However, there are still certain issues with its application. We sought this study is to systematically review and summarize studies pertaining blood laboratory biomarkers for diagnosing COVID-19. Methods: The systematic review was conducted by following the PRISMA 2020 recommendations. We searched published articles in four databases (EbscoHost, Pubmed, Science Direct, and Scopus).that assessed the implementation of routine laboratory tests examination for diagnosing COVID-19 patients from March 2020 through September 2021. Results: Three studies were selected to be reviewed, with the number of participants ranging from 100 to 485 (total: 792). Peripheral blood count parameters were assessed in all studies. The monocyte-lymphocyte ratio had the highest accuracy. Several abnormalities of laboratory indicators such as white blood cell, neutrophil, lymphocyte, eosinophil, NLR, MLR, LDH, AST, ALT, and CRP were significantly different between COVID-19 positive patients to negative controls,. Conclusion: No single test could identify or distinguish COVID-19 from other pneumonia causes. However, laboratory biomarkers can be used as a complement to the COVID-19 diagnostic approach.